Comunidade de machos de Euglossina (Hymenoptera: Apidae) e avaliação da suficiência amostral dos métodos tradicionais de coleta para a sua captura em área de Cerrado no Nordeste Brasileiro, Balsas, MA - MENDONÇA, Márcio Wésley Alves (2012)
A community of orchid bees from Northeast Cerrado was investigated in relation to the species composition and response to two methods of traditionally employed survey, scent baits end insect net, during the period from November/2010 to September/2011. A total of 1705 Euglossina males belonging to four genera and 18 species have also resulted from complementary efforts. The two methods of collecting evaluated have sampled 292 individuals, 14 species. Scent baits captured 83 individuals and 12 species, while the insect nets captured 209 individuals and 11 species. Two species were sampled exclusively on net, while three species were sampled exclusively on scent traps. Both richness and abundance were significantly different between the sampling methods. Insect net method captured more individuals and species per point than the trap and proved to be about four times higher on average than the scent bait method. The highest richness was found in the rainy season. Three new records are described for the Brazilian Cerrado, Euglossa (Euglossa) despecta (Moure), Eulaema (Apeulaema) pseudocingulata (Oliveira) and Eulaema (Eulaema) meriana (Oliver). The non- parametric estimators for the total effort indicate that about 1⁄4 of Euglossina species that inhabit the study area were not captured. This study suggest that although the method of nets has been shown superior, the scent baits alone when adapted to cover large areas, increasing the number of sampling points, it can provide a good sampling of the fauna of these bees in Cerrado under the conditions of the present study.